Study of the Potential and Development of a Mangrove Ecosystem Based on Ecotourism in Pinasungkulan Village, Minahasa Regency - Bonde, Alis Febri; Boneka, Farnis B. Boneka; Schaduw, Joshian N. W.; Makapedua, Daisy Monica; Rumengan, Antonius Petrus; Manoppo, Victoria E. N. (Jurnal Ilmiah Platax, 2024)
This research aims to describe the ecological, socio-economic, institutional, and infrastructural conditions. Primary data collection was carried out through direct observation in the field, measuring the potential of mangrove forests, observing biota, and conducting direct interviews with local communities and relevant stakeholders. Secondary data collection was conducted by gathering documents from previous studies/research, legislation, and other supporting data. Four types of mangroves were found: Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, and Avicennia marina. The highest species density was Rhizophora apiculata with 6.56 individuals/m², the highest species frequency was 1 for Rhizophora apiculata, the highest species coverage value was Sonneratia alba at 34.02, and the highest Importance Value Index (IVI) was Rhizophora apiculata at point 3 with a value of 226.98. The mangrove diversity index (H') was 2.66, indicating a moderate category and the highest evenness index was at point 2, with a value of 0.92. The Mangrove Tourism Suitability Index (IKW) value was 2.36, indicating a Suitable category. The mangrove area in Pinasungkulan Village can accommodate a 350 square meter mangrove tracking area. The Area Carrying Capacity (DDK) is 56 people per day, with an operational time of 8 working hours per day. The study on community perceptions regarding the benefits of the mangrove ecosystem and its potential to be developed as an ecotourism destination is very positive, and it is expected that this can improve the community's welfare in Pinasungkulan Village. Keywords: ecotourism, mangroves, carrying capacity, suitability, Pinasungkulan Abstrak Penelitian ini bertujuan mendeskripsikan kondisi ekologi, sosial ekonomi, kelembagaan dan infrastruktur. Pengumpulan data primer dilakukan melalui pengamatan langsung (observasi) di lapangan, melalui pengukuran potensi hutan mangrove, pengamatan biota dan wawancara langsung dengan masyarakat lokal dan pihak terkait. Pengumpulan data sekunder dilakukan dengan cara mengumpulkan dokumen hasil studi/penelitian, peraturan perundang-undangan dan data pendukung lainnya. Terdapat 4 jenis mangrove yang ditemukan yaitu Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba dan Avicennia marina. Nilai kerapatan jenis tertinggi adalah Rhizophora apiculata yaitu 6,56 individu/m², frekuensi jenis tertinggi adalah 1 pada jenis Rhizophora apiculata, nilai penutupan jenis tertinggi Sonneratia alba yaitu 34,02, Indeks Nilai Penting (INP) tertinggi jenis Rhizophora apiculata di titik 3 dengan nilai 226,98, indeks keanekaragaman mangrove H’= 2,66 dengan kategori sedang, indeks kemerataan tertinggi pada titik 2 yaitu 0,92. Nilai Indeks Kesesuaian Wisata (IKW) mangrove 2,36, menunjukkan kategori Sesuai. Kawasan mangrove Desa Pinasungkulan dapat dibangun tracking mangrove seluas 350 meter². Daya Dukung Kawasan (DDK) adalah 56 orang/hari dengan waktu operasional 8 jam kerja per hari. Kajian persepsi masyarakat tentang manfaat ekosistem mangrove dan potensinya untuk dikembangkan sebagai tujuan ekowisata sangat baik sehingga diharapkan hal tersebut dapat meningkatkan kesejahteraan masyarakat di Desa Pinasungkulan. Kata kunci: ekowisata, mangrove, daya dukung, kesesuaian, pinasungkulan